THE EFFECTS OF WORK-LEISURE CONFLICT, WORK OVERLOAD AND WORK-FAMILY CONFLICT ON JOB EMBEDDEDNESS: MODERATING ROLE OF PERCEIVED SUPERVISOR SUPPORT - PUTRIWULANDARI, FATHIYAH DAMAR; SUDJADI, ACHMAD; INDRAYANTO, ADI (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this research was to find out the effect of work-leisure conflict, workoverload, work-family conflict on job embeddedness using perceived supervisor support asthe moderating variable. The number of respondents in this research were 81 employees ofBank Mandiri, Fatmawati. Purposive sampling method is used to determine sample of thisresearch. Based on result of the research and data analysis using Moderated RegressionAnalysis techniques with the help of SPSS software to ran the data, it was revealed that: (1)work-leisure conflict has a negative and significant effect on job embeddedness, (2) workoverload has no effect on job embeddedness, (3) work-family conflict has a negative andsignificant effect on job embeddedness, (4) perceived supervision support did not moderatethe negative effect of work-leisure conflict and work-family conflict on job embeddedness (5)perceived supervisor support moderate the negative effect of work overload to jobembeddedness.